Comparative Analysis of Sharia Business Management in Various Industrial Sectors - Widya Khaidir; Husain Nurisman; Xie Guilin; Deng Jiao (Yayasan Adra Karima Hubbi, 2024)
In the midst of increasing interest and growth in sharia-based industries in various sectors, research on sharia business management is becoming increasingly important. Indonesia sees great potential in sharia economics as a substitute for an ethical and sustainable economic system. The main objective of this research is to find out how sharia management principles are applied in various industries and to find different and similar ways. IThis study was conducted using qualitative methods and comparative case studies. Data was collected through in-depth interviews with managers and executives in retail, food and beverage, banking and tourism businesses. In addition, secondary data was obtained from academic publications, industry publications, and company annual reports.. The research results show that the application of sharia business management in various industries varies. The level of compliance of the sharia banking sector with sharia principles is very high, especially in terms of financial transactions and banking products. The food and beverage and retail sectors place more emphasis on halal aspects in the supply chain and products sold, while sharia tourism places more emphasis on service and experience aspects that are in line with Islamic values. This study found that sharia business management has many applications, depending on the characteristics and needs of each industry.